Development of a two wheels inverted pendulum mobile robot - Nawawi, Sophan Wahyudi (2007)
The research on two-wheeled inverted pendulum (T-WIP) mobile robots or commonly known as balancing robots have gained momentum over the last decade in a number of robotic laboratories around the world. This paper describes the hardware design of such a robot. The objective of the design is to develop a T-WIP mobile robot to be used as flexible platform comprises of embedded unstable linear plant intended for research and teaching purposes. Issues such as selection of actuators and sensors, signal processing units, modeling and control scheme was addressed and discussed. The system is then tested using a well-known pole-placement state feedback controller to verify its functionality.